Decreased Circulating Insulin-Like Growth Factor 1 Levels Are Associated with Cardiac Diastolic Dysfunction in Small for Gestational Age Infants - Akazawa, Yohei; Yamazaki, Shoko; Obinata, Haruka; Hachiya, Akira; Kamiya, Motoko; Motoki, Noriko; Nakamura, Tomohiko (American Journal of Perinatology, 2018)
Objective To evaluate the impact of serum insulin-like growth factor-1 (IGF-1) levels on cardiac function in small for gestational age (SGA) infants.Study Design This is a prospective, observational study. Serum IGF-1 levels at birth and echocardiography measurements at 1 week of age were compared between SGA and appropriate for gestational age (AGA) infants.Results Thirty-one SGA infants and 27 AGA infants were enrolled. Serum IGF-1 levels were lower in the SGA infants than in the AGA infants. SGA infants had lower mitral lateral annular systolic (S') and early diastolic (E') tissue Doppler imaging velocities compared with AGA infants (S', 5.1 ± 0.9 vs 5.7 ± 1.2 cm/s; E', 6.1 ± 1.5 cm/s vs 7.1 ± 1.3 cm/s; p < 0.05). Serum IGF-1 levels positively correlated with E' velocity in the entire population (r = 0.44, p < 0.001) and in SGA infants (r = 0.39, p < 0.05). In multivariate linear regression analysis, serum IGF-1 and S' velocity were independently associated with E' velocity in the entire population and in SGA infants.Conclusion Decreased serum IGF-I levels could account for cardiac diastolic dysfunction in SGA infants.
Keywords: fetal programming; intrauterine growth restriction; small for gestational age infant; insulin-like growth factor-1; cardiac dysfunction; systolic–diastolic coupling